A study of reaction between palladium, palladium silver alloy and silicon carbide ceramics at high temperature. Issue 8 (July 2023) - Liu, Han; Chen, Ying; Gao, Zhaohe; Rohbeck, Nadia; Xiao, Ping
Abstract: The reactions between palladium (Pd), palladium-silver alloy (Pd-Ag) and silicon carbide (SiC) from 1200 °C to 1400 °C have been studied to investigate the impact of liquid phases on reaction products formation. The liquid phases were generated in Pd/SiC reactions at 1400 °C and in Pd-Ag/SiC reactions above 1300 °C. An increase in the amount of liquid associated with higher temperatures or Ag presence strongly affected the reaction mechanism and was responsible for the inhomogeneous dissolution of SiC grains and grain boundaries by Pd-rich phase at reaction front. This study helps understand Pd's role on Ag release through SiC layer in Tri-structural isotropic (TRISO) fuel particles.